AKTIVITAS ANTIBAKTERI BUNGA GALA-GALA MERAH (SESBANIA GRANDIFLORA L.) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS EPIDERMIDIS - Yasinta Moi, Maria; Ulia Rita Sila, Vinsensia (Universitas Cokroaminoto Palopo, 2024)
Gala-gala is known to have many benefits as a medicinal plant that can cure some kinds of diseases. People in Timor Island, East Nusa Tenggara, use red gala-gala flowers as a source of vegetables and medicines to cure infectious diseases such as itching that causes abscesses. This study aims to find out the antibacterial activity of red gala-gala flower extract to inhibit the growth of Staphylococcus epidermidis bacteria. The method of antibacterial activity test used paper disk diffusion with concentrations of 20% and 40%. Antibacterial activities are shown by the presence of a halo zone around the agar surface that contains the test bacteria. The results were the average diameter of the barrier zone in 20% concentration at 9.11 mm, 40% at 10.76 mm, and the positive control at 30.46 mm. Also, there were no halo zones in the negative control. Based on the results, it can be concluded that red gala-gala flower extract possesses antibacterial activity in the sensitive category because it can inhibit the growth of bacteria within the diameter of the barrier zone produced by 10-15 mm. Thus, the red gala-gala flower can be used as one of the sources of natural bioactive anti-bacterial compounds to heal caused by microorganisms